Prediction of efficacy to pegylated interferon‐α‐2b plus ribavirin in patients with genotype 2 hepatitis C virus using viral response within 2 weeks. Issue 2 (27th March 2013) - Wada, Yuki; Tamai, Hideyuki; Uno, Akiko; Kawashima, Akira; Shingaki, Naoki; Mori, Yoshiyuki; Moribata, Kosaku; Miyata, Kaori; Higashi, Katsuhiko; Deguchi, Hisanobu; Ueda, Kazuki; Inoue, Izumi; et al.
<x xml:space="preserve">Abstract</x> Aim Rapid virological response (RVR), defined as serum hepatitis C virus (HCV) RNA negativity at 4 weeks, is the most useful predictor of sustained virological response (SVR) to standard pegylated interferon (PEG IFN) plus ribavirin therapy for patients infected with genotype 2 HCV. The aim of the present study was to predict SVR using viral response within 2 weeks of therapy initiation. Methods Of 64 HCV genotype 2 patients with a high viral load treated with standard PEG IFN‐α‐2b plus weight‐based ribavirin for 24 weeks, 58 patients whose adherence was more than 67% were analyzed. RNA and core antigen levels were measured at four time points: the day of therapy initiation, the following day, and at 1 and 2 weeks. Results SVR was achieved in 73% (47/64) of patients. Univariate analysis of SVR contributing factors showed significant differences with age, bodyweight, white blood cell count, platelet count, fibrosis marker levels, baseline core antigen level and viral response. The area under the receiver–operator curve (AUC) of the core antigen level at 1 week (AUC, 0.940) was the highest among the significant SVR predicting factors. Setting 100 fmol/L as the cut‐off value for core antigen level at 1 week, the sensitivity, specificity, positive predictive value, negative predictive value and accuracy for predicting SVR were 100%, 86%, 96%, 100% and 97%, respectively, and for predicting RVR were 66%, 93%, 97%, 46% and 72%, respectively. Conclusion The HCV core antigen level at 1 week after therapy initiation is the most useful predictor for SVR.